Urban ecologies : city space, material agency, and environmental politics in contemporary culture - Schliephake, Christopher, 1985- (Ecocritical theory and practice., 2015)
This book provides a reflection on urban ecocriticism, a subject that has yet to be fully researched and appreciated within the trans-disciplinary framework of the environmental humanities.